HADITS RASULULLAH SAW TENTANG FAKTOR YANG MEMPENGARUHI PENDIDIKAN - Abdul Wahab Syakhrani; Histy Histy; Khatimatul Husna; Mujibah Mujibah; Norhaliza Norhaliza (ADIBA : JOURNAL OF EDUCATION, 2022)
Children are family members where parents are the family leaders as responsible for the safety of their children both in this world and in the hereafter, so parents are obliged to educate their children. The child takes an example from his family members, to his father, to his mother or to his siblings, so parents in the family must pay attention to their children and educate them.